True crime podcasting: Journalism, justice or entertainment?. (1st October 2019) - Boling, Kelli S.
This study examines true crime podcasts with a critical/cultural lens to explore how podcasts are impacting the true crime genre, public opinion and the criminal justice system. Four in-depth qualitative interviews with true crime podcast producers offer insight into both the political economy of podcasts and effective audience engagement. Ultimately, this study argues that true crime podcasts are impacting the criminal justice system in unprecedented ways and that the future of this emerging media could challenge both criminal justice and media reform. Practical implications for genre-specific media are also discussed.